Surface Plasmon Resonance Microscopy: Correlating Surface Plasmon Resonance Microscopy of Living and Fixated Cells with Electron Microscopy Allows for Investigation of Potential Preparation Artifacts (Adv. Mater. Interfaces 6/2020). Issue 6 (20th March 2020) - Kreysing, Eva; Seyock, Silke; Hassani, Hossein; Brauweiler‐Reuters, Elke; Neumann, Elmar; Offenhäusser, Andreas
Abstract : In article number 1901991, Eva Kreysing, Andreas Offenhäusser, and co‐workers use surface plasmon resonance microscopy to confirm the conservation of the 3D structure of the basal cell membrane (center) throughout chemical fixation. Correlation with electron microscopy images of the cross‐section of the same cells reveals artifacts caused by further sample preparation.